Synthesis of imidazol-1-yl-acetic acid hydrochloride: A key intermediate for zoledronic acid - Singh, Santosh Kumar; Manne, Narendra; Ray, Purna Chandra; Pal, Manojit (Beilstein Journal of Organic Chemistry, 2008)
A convenient and practical synthesis of imidazol-1-yl-acetic acid hydrochloride was achieved via N-alkylation of imidazole using tert-butyl chloroacetate followed by a non-aqueous ester cleavage of the resulting imidazol-1-yl-acetic acid tert-butyl ester in the presence of titanium tetrachloride. The synthesized imidazol-1-yl-acetic acid hydrochloride was then utilized to prepare zoledronic acid.
Keywords: ester; N-alkylation; imidazol-1-yl-acetic acid hydrochloride; zoledronic acid